Effect of adding natural coconut oil on the antifungal, flexural strength, and hardness properties of heat cure acrylic resin (an in vitro study) - Amrah Y. Al-Jmmal (Romanian Journal of Stomatology)
Purpose. This study's objective was to estimate the effect of various quantities of the addition of natural coconut oil according to concentrations (1%, 2%, 3%) on the heat cured denture base material's anti-fungal, flexural strength, and hardness properties. Material and method. A total of 120 samples were created and (divided into three groups each groups contain forty samples) built regarding the attitude test: Candida albicans adherence test, flexural strength test, and hardness test. Next, each group was subdivided into three subgroups (control 0%, 1%, 2% and 3%) based on the various quantities of the added natural coconut oil, with (n=10 samples for each subgroup). Each group was assessed at 48 hours. One-way ANOVA and other statistical methods were used to analyze the data, Duncan and Dunnett’s tests for comparison means among all groups with control at p ≤0.05. Results. A One-way ANOVA showed a significant difference in the mean values of Candida albicans adherence, with the additive of natural coconut oil groups (1%, 2%) showing the highest antifungal effect compare with (3% additive groups). Adding 1% coconut oil had no significant difference on hardness and flexural strength, while adding 2% and 3% additive of coconut oil groups showed a significantly decrease than control groups at p ≤ (0.05). Conclusion. The antifungal properties of heat-cured acrylic resin are enhanced by the addition of coconut oil. However, when used in high concentrations (greater than 1%), it can result in a decrease in hardness and flexural strength.